Differential physiological and yield responses of selected mung bean (Vigna radiata (L.) R. Wilczek) genotypes to various high-temperature stress regimes - Uday Chand Jha; Sadiah Shafi; Shyam Tallury; Harsh Nayyar; Ignacio A. Ciampitti; Kadambot H. M Siddique; P. V. Vara Prasad (Scientific Reports)
Abstract The increasing frequency of heat stress events due to climate change disrupts all stages of plant growth, significantly reducing yields, especially in crops like mung bean (Vigna radiata (L.) R. Wilczek). Mung beans are vital grain legumes in Southeast Asian countries and are crucial for food security. Thus, it is essential to understand the physiological and yield-related trait responses of mung bean genotypes and harness germplasm with enhanced heat tolerance to mitigate the impact of rising heat stress on mung bean yield. This study assesses the physiological and yield-related responses of ten diverse mung bean genotypes grown under three temperature regimes (34/25 °C, 39/30 °C, and 42/30 °C) in three growth chambers. We found significant genetic variability in phenological, physiological, and yield-related traits under control and heat stress conditions. Severe leaf damage, indicated by high cell membrane injury, reduced chlorophyll index, and diminished chlorophyll fluorescence, was observed under 39/30 °C and 42/30 °C conditions. Similarly, significant reductions in yield component traits, including effective pods per plant, total seeds per plant, single-seed weight, and seed yield per plant, were evident in the tested genotypes under 39/30 °C and 42/30 °C conditions. Correlation analysis suggested that selecting genotypes with higher chlorophyll index and increased canopy temperature depression could help identify mung bean varieties with enhanced pod and seed yields under heat stress. Clustering analysis identified genotypes PI 425425, PI 425238, and PI 363361 as potential candidates for breeding programs to develop climate-resilient cultivars.